2011
DOI: 10.1111/j.1439-0485.2011.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Acesta clams from submarine seamounts and escarpments along the western margin of North America

Abstract: Genetic connectivity and habitat characteristics were examined in two species of Acesta clams (Bivalvia: Limidae) from submarine seamounts and continental slopes along the western North America margin. Two species were identified from dive videos obtained with submarine remotely operated vehicles that surveyed a 2200‐km range between 27° and 46° N latitude. Acesta sphoni was only found at shallower habitats (545–860 m depth) in the southern part of this range, whereas Acesta mori was more abundant and widely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…nov. more closely with A. bullisi and A. oophaga from the Gulf of Mexico, and A. mori from the northeast Pacific, suggesting a more recent affinity than with A. excavata. Furthermore, A. mori (Hertlein, 1952) (Clague et al 2012) appears to be morphologically and genetically closer to the North Atlantic "excavata" group than to A. sphoni, its northeast Pacific sibling, which is morphologically more similar to A. smithi, a southwestern Pacific species included in the subgenus Plicacesta by Hertlein (1963) and Vokes (1963). Here as well, further genetic studies may help resolve the evolutionary origin of these species within the Atlantic and Pacific Oceans.…”
Section: Discussionmentioning
confidence: 99%
“…nov. more closely with A. bullisi and A. oophaga from the Gulf of Mexico, and A. mori from the northeast Pacific, suggesting a more recent affinity than with A. excavata. Furthermore, A. mori (Hertlein, 1952) (Clague et al 2012) appears to be morphologically and genetically closer to the North Atlantic "excavata" group than to A. sphoni, its northeast Pacific sibling, which is morphologically more similar to A. smithi, a southwestern Pacific species included in the subgenus Plicacesta by Hertlein (1963) and Vokes (1963). Here as well, further genetic studies may help resolve the evolutionary origin of these species within the Atlantic and Pacific Oceans.…”
Section: Discussionmentioning
confidence: 99%
“…Clams collected in the Clague et al (2012) study were used for molecular analysis; the shells were not used for morphological analysis until this study. Shells were cleaned, dried, and measured with calipers to nearest 0.01 mm for height (H), width (W) and shell inflation (I), as described in Figure 2 and by Järnegren et al (2007) and Carter et al (2012).…”
Section: Shell Morphologymentioning
confidence: 99%
“…Previously, Acesta agassizii (Dall, 1902) was the only file clam species reported in the GoC (Coan & Valentich-Scott, 2012). Clague et al (2012) reported that videos obtained during a 2003 MBARI expedition to the GoC revealed clams tentatively identified as Acesta cf. sphoni, but specimens were not collected for taxonomic or molecular identification.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such isolation might arise due to the patchiness of the seamounts habitats (particularly of active seamounts as most seamounts are inactive), combined with larval behaviors, physical oceanographic phenomena, such as Taylor Other studies in non-vent seamount fauna have found similar patterns of absence of population structuring among seamount populations of deep-sea corals (Thoma et al 2009), clams (Clague et al 2012), and ophiuroids (Cho & Shank 2010), when examining mitochondrial markers. However, the mitochondrion has a intermediate mutation rate compared to other autosomal markers such as microsatellites and single nucleotide polymorphisms (SNPs), and mounting evidence indicates that significant amounts of genetic variability in populations and species can go undetected based solely on mitochondrial data Herrera & Shank Chapter 5).…”
Section: Introductionmentioning
confidence: 95%